(untitled) (Medical Forum Monthly, 2024)
Objective: To study the micro structural changes in the kidney of the offspring’s of Swiss albino mice exposed to smokeless tobacco during pregnancy. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conduct at the Animal House of the Department of Animal Husbandry and Veterinary Sciences (AHVS) Sindh Agriculture University, (SAU) Tandojam from July 2015 to December 2015. Materials and Methods: Healthy adult female mice were mated. After confirmation of pregnancy, 20 pregnant mice were categorized into two categories, experimental group A and control group B. Group-A was provided Tobacco 5% mixed with standard diet along with clean water ad libitum, whereas group B, the control was provided standard diet and clean water ad-libitum throughout their pregnancy. After birth 20 offspring (10 male & 10 female) were selected randomly from each group. At 15 days after birth, the offspring were sacrificed by cervical dislocation and their kidneys were dissected out for histological analysis. Results: The histological marked changes were seen in the kidney of offspring’s of mice. In the experimental group of offspring there were very few glomeruli and also more immature glomeruli were observed. Glomerular degenerative changes, micro calcifications were noticed in both female and male offspring’s of experimental group. Fatty change was observed in the renal parenchyma of the experimental group in 14 animals 9 male and 5 female offspring’s showed edematous change and fatty infiltration. Glomerulus architectural distortion and displacement were also seen in kidneys of both offspring’s. Conclusion: Consumption of smokeless tobacco having significant effects on structure of kidney of offspring of mice that presented with the cellular injury to kidney parenchyma especially fatty infiltration as well asglomerular distortion and degenerative changes.